Correlated individual differences suggest a common mechanism underlying metacognition in visual perception and visual short-term memory. Issue 1867 (22nd November 2017) - Samaha, Jason; Postle, Bradley R.
Abstract : Adaptive behaviour depends on the ability to introspect accurately about one's own performance. Whether this metacognitive ability is supported by the same mechanisms across different tasks is unclear. We investigated the relationship between metacognition of visual perception and metacognition of visual short-term memory (VSTM). Experiments 1 and 2 required subjects to estimate the perceived or remembered orientation of a grating stimulus and rate their confidence. We observed strong positive correlations between individual differences in metacognitive accuracy between the two tasks. This relationship was not accounted for by individual differences in task performance or average confidence, and was present across two different metrics of metacognition and in both experiments. A model-based analysis of data from a third experiment showed that a cross-domain correlation only emerged when both tasks shared the same task-relevant stimulus feature. That is, metacognition for perception and VSTM were correlated when both tasks required orientation judgements, but not when the perceptual task was switched to require contrast judgements. In contrast with previous results comparing perception and long-term memory, which have largely provided evidence for domain-specific metacognitive processes, the current findings suggest that metacognition of visual perception and VSTM is supported by a domain-general metacognitive architecture, but only when both domains share the same task-relevant stimulus feature.